2009
DOI: 10.1016/j.jvs.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The care of patients with an abdominal aortic aneurysm: The Society for Vascular Surgery practice guidelines

Abstract: DEFINITION OF THE PROBLEM Purpose of these guidelinesThe Clinical Practice Council of the Society for Vascular Surgery charged a writing committee with the task of updating practice guidelines, initally published in 2003, for surgeons and physicians who are involved in the preoperative, operative, and postoperative care of patients with abdominal aortic aneurysms (AAA). 1 This document provides recommendations for evaluating the patient, including risk of aneurysm rupture and associated medical co-morbidities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
520
1
27

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(576 citation statements)
references
References 510 publications
(562 reference statements)
2
520
1
27
Order By: Relevance
“…Recent studies have extended this work into the area of abdominal aortic aneurysm, to determine whether inflammation might be a predictor of rapid aneurysm expansion or heightened rupture risk. Current guidelines for stable patients recommend surgical or endovascular intervention based largely on aortic dimensions [82,83], although it is well known that rupture can occur in small aneurysms as well. It has been shown that abdominal aortic FDG uptake is associated with higher wall stress [84] and correlates with instability, symptoms and with macrophage infiltration [85].…”
Section: The Potential Of Fdg-pet Imaging In Aortic Aneurysm and Aortmentioning
confidence: 99%
“…Recent studies have extended this work into the area of abdominal aortic aneurysm, to determine whether inflammation might be a predictor of rapid aneurysm expansion or heightened rupture risk. Current guidelines for stable patients recommend surgical or endovascular intervention based largely on aortic dimensions [82,83], although it is well known that rupture can occur in small aneurysms as well. It has been shown that abdominal aortic FDG uptake is associated with higher wall stress [84] and correlates with instability, symptoms and with macrophage infiltration [85].…”
Section: The Potential Of Fdg-pet Imaging In Aortic Aneurysm and Aortmentioning
confidence: 99%
“…Abdominal Aortic Aneurysm (AAA) is the most common form of aortic aneurysms that results from degradation of medial elastin of the atheromatous aorta 11, 12…”
Section: Discussionmentioning
confidence: 99%
“…16 The current tendency is to preserve pelvic flow when treating aortoiliac aneurysms, even when internal iliac arteries are involved, and specific directives for management and treatment of aneurysmal aortoiliac disease suggest that at least one internal iliac branch should be preserved. 17,18 Studies have been published showing good results in terms of preservation of flow to an iliac branch and reporting technical success and low morbidity with the procedure. 10,11,19,20 The majority of significant complications described after implantation of these devices are related to acute occlusion of the iliac branch.…”
Section: Discussionmentioning
confidence: 99%